Burnout, hardy personality, and psychological distress in nursing personnel - Ríos Rísquez, María Isabel; Godoy Fernández, Carmen; Sánchez Meca, Julio (Anales de Psicología / Annals of Psychology, 2010)
The aim of this research was to analyze the relevance of individual variables in the development of burnout, as well as the possible effects of „hardiness‟ or „hardy personality‟ as a protective factor against burnout and its consequences on workers‟ health. The sample was composed of 97 nursing professionals belonging to the intensive care and emergency units in a hospital. Four assessment instruments were applied to the participants: an ad hoc questionnaire of sociodemographic and work variables, a Spanish version of the General Health Questionnaire (GHQ- 28), a Spanish adaptation of the Maslach Burnout Inventory (MBI), and the Hardy Personality Scale (CPR) of the Nursing Burnout Questionnaire (CDPE). The results confirmed the relationship between hardy personality and burnout, as well as the health consequences of the latter. Finally, the clinical implications of the results are discussed, as well as some recommendations for future research in this field.